Pengaruh Imbangan Tepung Umbi Ganyong dan Tepung Umbi Garut terhadap Karakteristik Cookies Gluten Free - Adithiya, Afif Rizky; Herlinawati, Lina (Ma'soem University, 2025)
The aim of this study was to determine the effect of the balance of arrowroot flour and ganyong tuber flour on the characteristics of gluten-free cookies, as well as the level of consumer preference for the resulting cookies. The research methodology used was a Randomized Block Design (RAK) consisting of five treatments and five replications. Analysis of variance (ANOVA) was used to examine the collected data, and if there were significant differences, continued with Duncan Multiple Range Test (DMRT) using a significance level of 5%. The results showed that the ratio of ganyong tuber flour and arrowroot flour had a significant effect on water content, fiber, carbohydrate, ash, color, texture but does not have a significant effect on taste and aroma. The balance with (100 Ganyong tuber flour : 0 Garut tuber flour) produces cookies with the best characteristics with a color preference value of 3.65 (neutral towards liking), taste 3.66 (neutral towards liking), aroma 3.73 (neutral towards liking), texture 3.49 (neutral towards liking), and water content of 1.90%, fiber 3.16%, carbohydrate 78.18%, and ash 1.37%. All balances have met SNI standards except fiber.